Investigating the Risk–Return Relationship of Information Technology Investment: Firm-Level Empirical Analysis - Dewan, Sanjeev; Shi, Charles; Gurbaxani, Vijay (Management Science, 2007)
This paper develops empirical proxy measures of information technology (IT) risk and incorporates them into the usual empirical models for analyzing IT returns: production function and market value specifications. The results suggest that IT capital investments make a substantially larger contribution to overall firm risk than non-IT capital investments. Further, firms with higher IT risk have a higher marginal product of IT relative to firms with low IT risk. In the market value specification, the impact of IT risk is positive and significant, and inclusion of the IT risk term substantially reduces the coefficient on IT capital. We estimate that about 30% of the gross return on IT investment corresponds to the risk premium associated with IT risk. Taken together, our results show that IT risk provides part of the explanation for the unusually high valuations of IT capital investment in recent research.